Optimizing the Banking Service System Using Queue Theory, Fuzzy DEMATEL and TOPSIS Approach: Case Study - Mohammad Forozandeh (Annals of Human Resource Management Research, 2022)
Purpose: This paper aimed to improve and optimize the overall performance of the banking service system using queue theory in various activities whilst maximizing profits. Research Methodology: Based on previous literature and interview with related experts, the initial status of the banking system is analyzed as well as the methodologies of queue theory. The data was analyzed to modeling queuing systems for understanding queuing behavior using Wittness Software for simulation. Different queuing strategies will be implemented using the waiting time to find the most efficient solution and the optimized result is concluded. Result: In this paper, the performance of the banking system is investigated and improved by the queuing theory. The sensitive analysis approach will provide new solutions for the optimization of the bank queuing, which could later be implemented for better banking performance. Based on the results obtained, the recommended method produces the best customer satisfaction and maximizes profits. The results of the paper enable decision-makers to obtain useful results with enough knowledge of the behavior of the system. Limitation: This research only described the Iranian bank system. There is different limitation regarded as external factors that varies from one banking system to another and many works are needed to further combat the problems faced by the banking sectors. Contribution: The results are a guideline for managers or decision makers and help them shorten cycle time and to save costs, and resolve problems. It also serves as a useful base for researchers to expand further research concerning the problems of the banking system in other organizations.